Evaluation of yield losses and management practices of false smut in rice (Oryza sativa) - J. KUMAR*, SNEHLATA KUMARI and (Indian Phytopathology, 2015)
Of the 24 rice varieties evaluated from different rice-growing areas in Uttarakhand and Uttar Pradesh, incidence of false smut disease ranged from 5.0 to 48.76%, while yield loss was 0.82-17.09%. Among these, hybrids were found to be more prone to false smut. Maximum disease incidence was observed in hybrids, PA 6444 (48.76%), followed by PSD-3 (32.81%) and PRH 10 (28.94%) with maximum yield loss of 17.09% in PA 6444. Field trials were conducted during 2012 and 2013 to test efficacy of new fungicides against false smut. The spraying of Propiconazole @ (0.1%) with first spray at booting stage and second at an interval of 10 days was most effective. Similarly, Trifloxystrobin + Tebuconazole (0.04%), Hexaconazole (0.2%), Carbendazim (0.1%) and Kreoxim methyl (0.1%) significantly reduced its incidence compared with the control. All fungicides were effective when applied at boot stage, except kreoxim methyl, which was found to be more effective when applied at heading stage.